Reading the European novel to 1900 : a critical study of major fiction from Cervantes' Don Quixote to Zola's Germinal - Schwarz, Daniel R. (Reading the novel., 2014)
" Offers a close reading of individual texts with attention to their cultural and canonical context Examines the history and evolution of the novel to 1900 and defines each author's aesthetic, cultural, political, and historical significance Covers essential and frequently taught masterworks up to 1900, including Cervantes' Don Quixote; Tolstoy's War and Peace and Anna Karenina; Dostoevsky's Notes from Underground, Crime and Punishment, and The Brothers Karamazov; Stendhal's The Red and the Black and The Charterhouse of Parma; Flaubert's Madame Bovary and Sentimental Education; Balzac's Pere Goriot; and Zola's Germinal Written with students and teachers in mind, this book provides accessible and engaging discussions of each novel, along with important pedagogical tools "--